New records and distribution expansions for neotropical water-striders (Insecta: Heteroptera: Gerromorpha) - Moreira, Felipe Ferraz Figueiredo; Ribeiro, José Ricardo Inacio; Nessimian, Jorge Luiz; Itoyama, Mary Massumi [UNESP]; Castanhole, Márcia Maria Urbanin [UNESP]; Pereira, Luís Lênin Vicente [UNESP] (Pensoft Publishers, 2011)
Based on material from several collections, summarized distributions and new records are presented for selected Neotropical species of Gerromorpha of the families Gerridae (Brachymetra albinervis albinervis, B. furva, B. lata, B. shawi, Cylindrostethus erythropus, C. linearis, C. palmaris, C. regulus, Halobatopsis platensis, Limnogonus aduncus aduncus, L. hyalinus, L. ignotus, L. profugus, L. recurvus, Neogerris lubricus, N. magnus, N. lotus, N. visendus, Ovatametra gualeguay, Rheumatobates crassifemur crassifemur, R. c. esakii, Tachygerris adamsoni, T. celocis and T. surinamensis), Hydrometridae (Hydrometra guianana and H. sztolcmani) and Mesoveliidae (Mesovelia amoena, M. mulsanti and Mesoveloidea williamsi).